Survival and Perioperative Outcomes After Addition of Immunotherapy to Neoadjuvant Chemoradiotherapy for the Treatment of Locally Advanced Esophageal Squamous Cell Carcinoma - Canjun Li; Xin Wang; Lei Deng; Jianyang Wang; Tao Zhang; Wenqing Wang; Wenyang Liu; Jima Lv; Qinfu Feng; Zongmei Zhou; Xiankai Chen; Ruixiang Zhang; et al. (Thoracic Cancer)
ABSTRACT Background Currently, neoadjuvant chemoradiotherapy combined with immunotherapy (NCRI) for patients with locally advanced esophageal squamous cell carcinoma (ESCC) is attracting attention. The purpose of this study was to compare the surgical outcomes and survival between patients receiving NCRI and neoadjuvant chemoradiotherapy (NCRT) followed by surgery. Methods This study retrospectively included patients with locally advanced ESCC and treated with NCRI or NCRT followed by esophagectomy. Two groups were compared for pathologic complete response (pCR) rate, R0 resection rate, and 3‐year recurrence‐free survival (RFS). Surgery time, the number of lymph nodes removed, postoperative complications, and 30‐day mortality were also compared. Propensity score matching (PSM) was performed to minimize the potential impact of confounding factors. Results After PSM, patients in the NCRI group showed a significantly higher pCR rate compared with those in the NCRT group (54.2% vs. 27.1%, p = 0.046). R0 resection rate (100% vs. 89.6%, p = 0.251), surgery time (p = 0.614), the number of lymph nodes removed (p = 0.526), the incidence of total postoperative complications (46.4% vs. 37.9%, p = 0.564) and 30‐day mortality (3.6% vs. 1.1%, p = 0.983) were comparable between the two groups. The NCRI group exhibited a significantly higher 3‐year RFS rate compared to the NCRT group (79.2% vs. 62.5%, p = 0.032). Conclusion For patients with locally advanced ESCC, NCRI showed a significantly higher pCR rate than conventional NCRT, without increased operative risk. NCRI followed by surgery exhibited a superior RFS compared to NCRT followed by surgery. Prospective studies are needed in the future.